Haploidy in tomato - N. A. Shmikova (Овощи России, 2009)
This article reviews means and a significance of homozygous lines production in tomato through haploid plant stage. The haploid plants can be originated both male and female cells of gametophyte. Comprehensive and analytical information concerning achievements for last 40 years was given disclosing successful experiences and challenges in plant haploid production through androgenesis and gynogenesis in tomato.